Placental tumor (chorioangioma) as a cause of polyhydramnios: a case report - Abdalla N; Bachanek M; Trojanowski S; Cendrowski K; Sawicki W (Dove Medical Press, 2014)
Nabil Abdalla, Michal Bachanek, Seweryn Trojanowski, Krzysztof Cendrowski, Wlodzimierz Sawicki Chair and Clinic of Obstetrics, Gynecology and Oncology, Second Faculty of Medicine, Medical University of Warsaw, Warsaw, Poland Abstract: Placental chorioangioma is the most common type of placental tumor. It is usually symptomless and may be associated with serious maternal and fetal complication when it reaches a large size. We presented a case of an angiomatous type of placental hemangioma diagnosed in the second trimester of pregnancy in a patient with polyhydramnios. A normal volume of amniotic fluid was successfully achieved by three amnioreductions with conservative management. The size of the placental tumor remained the same from the time of diagnosis to the end of pregnancy. A term labor was uncomplicated and a healthy newborn was delivered. Macroscopic and microscopic examination of the placenta confirmed the diagnosis. Despite the rarity of placental tumors, they should be considered as differential diagnosis in cases of polyhydramnios. Keywords: amnioreduction, pregnancy disorders, ultrasonography placental tumor, chorioangioma